2023
DOI: 10.5187/jast.2022.e100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary organic trace minerals on enteric methane emissions and rumen microbiota of heat-stressed dairy steers

Abstract: Influence of dietary organic trace minerals on enteric methane emissions and rumen microbiota of heat-stressed dairy steers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Mineral bolus type was not associated with changes in the bacterial community composition or any rumen parameter. Our results are consistent with studies which have shown that mineral supplementation did not significantly alter bacterial abundances in dairy steers (Son et al, 2023) and yak (Bos grunniens) (Zhao et al, 2022). In contrast, other studies have shown a response to specific minerals.…”
Section: B a Figuresupporting
confidence: 92%
“…Mineral bolus type was not associated with changes in the bacterial community composition or any rumen parameter. Our results are consistent with studies which have shown that mineral supplementation did not significantly alter bacterial abundances in dairy steers (Son et al, 2023) and yak (Bos grunniens) (Zhao et al, 2022). In contrast, other studies have shown a response to specific minerals.…”
Section: B a Figuresupporting
confidence: 92%
“…Following a supplementation of lactating yaks with inorganic TM via slow release rumen boluses, some variations in the ruminal bacterial communities were observed, however the specific TM responsible for the changes was not clearly identified [86]. In a recent study with heatstressed dairy steer [77], supplementing high levels of organic TM (28 and 350 mg/kg DM of Cu and Zn as Cu-and Znglycinate, respectively), no effects were registered on enteric CH4 production or rumen methanogenic microbial populations [77].…”
Section: 6 Trace Mineral Effects On Rumen Microbiotamentioning
confidence: 99%
“…Ruminant productivity is significantly impeded by unfavourable climatic circumstances, particularly HS. HS decreases the amount of dry matter intake, which in turn, impairs the metabolism of energy and protein, resulting in higher levels of metabolic disorder, mineral imbalance, and several other health issues [ 103 ]. The temperature–humidity index (THI) is frequently used to assess thermal comfort in dairy cows.…”
Section: Methane Emissions and Heat Stress In Dairy Cowmentioning
confidence: 99%